PENERAPAN METODE REWARD DAN PUNISHMENT UNTUK MENINGKATKAN KEDISIPLINAN PESERTA DIDIK KELAS 5 DI TPA MADRASAH RIYADHUS SHALIHIN - Widya Rahmayanti; Abdul Qodir (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2023)
Disciplinary character is very important to be owned by humans so that other good character values emerge. The importance of strengthening the value of disciplinary character is based on the reason that there are behaviors that are contrary to the norms of discipline. Behavior that is contrary to the norm of discipline is found in various fields, especially in the field of education. The existence of student behavior that violates discipline is a discussion in almost all formal and non-formal educational institutions. Conditions at TPA Madrasah Riyadhus Sholihin are still many students who violate disciplinary rules so as to hamper the teaching process at TPA Madrasah Riyadhus Sholihin. One way to foster the discipline character of students by using the reward and punishment method through class action research. With the acquisition of cycle I, the results of children's order in very good criteria only reached 17% (2 children), good enough criteria reached 50% (6 children), poor criteria reached 25% (3 children), and 1 child was absent with a percentage of 8%. Whereas in cycle II there was an increase in the acquisition of student order with very good criteria reaching 58% (7 children), good enough criteria reached 8% (1 child), poor criteria reached 25% and 1 child was absent with a percentage of 8%.